A model of parental investment in children's human capital - Yueh, L (ESRC Centre on Sills, Knowledge and Organisational Performance (SKOPE), 2001)
Parents' decision to invest in children's human capital is motivated by returns to education and future transfers, which are both affected by perceived gender earnings differentials. To the extent that human capital is accumulated during a time in which the decision lies largely with parents, this model may contribute to understanding differential expenditure on the education of sons and daughters that cause human capital differences prior to entering the labour market.